Exploring Emotional Intelligence Of The Lead Character In To All Of The Boys I've Loved Before Novel - Jeniffer Gabriellen; Gede Primahadi Wijaya Rajeg; Ketut Santi Indriani (Denpasar Institute, 2026)
Emotional intelligence is a crucial factor in understanding how individuals perceive, manage, and express emotions in various aspects of life. This study aimed to analyze the portrayal of emotional intelligence in the main character of the novel To All the Boys I’ve Loved Before novel by Jenny Han. Using a qualitative approach, the analysis examines the five core components of emotional intelligence as outlined by Daniel Goleman: self-awareness, self-regulation, motivation, empathy, and social skills. Data were collected through documentation and note-taking techniques, to identify narrative moments that reflect emotional responses and interpersonal dynamics. The study explores how these components are demonstrated through the actions, thoughts, and interactions of Lara Jean Covey. The findings show that Lara Jean exhibits all five components of emotional intelligence, with self-awareness and empathy appearing most prominently. Her emotional responses become more complex over time, highlighting how emotional intelligence shapes her decisions, relationships, and internal reflections throughout the novel.